Azacitidine in outpatient treatment – single center experience - Rybka, Justyna; Stefanko, Ewa; Bogucka-Fedorczuk, Aleksandra; Butrym, Aleksandra; Poręba, Rafał; Kuliczkowski, Kazimierz; Wróbel, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study : Azacitidine is a hypomethylating agent which is used in the treatment of myelodysplastic syndromes, acute myeloid leukemia and chronic myelomonocytic leukemia. Because of good tolerance to the drug, azacitidine can be administered both during hospitalization and in an outpatient setting. The aim of our retrospective analysis was to assess the efficacy of azaciti-dine treatment in patients with a myelodysplastic syndrome and with acute myeloid leukemia who had received treatment in hospital and in an ambulatory care setting. Offsets in the course of azacitidine administration and discontinuations of treatment have a negative impact on patients’ response to the therapy. Material and methods: The study included 31 patients. Sixteen patients received azacitidine in an ambulatory care setting, 15 patients within their hospitalization. Results : A hematologic response was achieved in 48% of the patients. Forty-one percent of the cycles were delayed. In an outpatient setting, 62% of the cycles were administered systematically, while during hospitalization the patients received 54% of cycles on time. Administrative problems caused the delay of 26% of the cycles. Conclusions : Azacitidine has a high tolerance level and a high safety profile which allows for its use in an outpatient care setting. Outpatient administration of azacitidine is feasible and safe without compromising efficacy.